Non-invasive tools for compensated advanced chronic liver disease and portal hypertension after Baveno VII – an update. Issue 3 (March 2023) - Segna, Daniel; Mendoza, Yuly P.; Lange, Naomi F.; Rodrigues, Susana G.; Berzigotti, Annalisa
Abstract: Non-invasive tests (NITs) and liver stiffness measurement (LSM) in particular, have entered clinical practice over 20 years ago as point-of-care tests to diagnose liver fibrosis in patients with compensated chronic liver disease. Since then, NITs use has evolved thanks to a large number of studies in all major etiologies of liver disease, and they have become important tools to stratify the risk of portal hypertension and liver-related events. The Baveno VII consensus workshop provided several novel recommendations regarding the use of well-established and novel NITs in the specific setting of portal hypertension screening, diagnosis and follow-up. The Baveno VII expert panels paid special attention to summarizing the existing data into simple clinical rules able to guide clinicians in their practice. The "rule of five" for LSM is a tool to stratify the risk of liver-related events, and LSM alone or in combination with platelet count, can be used now to rule-in and rule-out compensated advanced chronic liver disease (cACLD) and clinically significant portal hypertension, as well as to rule-out high-risk varices. Use of NITs in obese subjects with non-alcoholic fatty liver disease (NAFLD) and patients with viral hepatitis C that has been successfully treated, require specific knowledge. This review will update the reader on these aspects.